2019
DOI: 10.1021/acs.orglett.9b01490
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Conulothiazole A

Abstract: An efficient total synthesis of the chlorinated thiazole-containing natural product conulothiazole A is reported. Key features of this synthesis include a novel rhodium-catalyzed enantioselective hydrogenation of a 2-enamido-thiazole and a vinylic Finkelstein reaction that could be implemented at all stages of the synthesis to install the chlorinated alkene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As an example of a synthetic application, Evano's group recently developed a short and modular total synthesis of Conulothiazole A in 7 steps and 30% overall yield. 292 One of the key steps was an efficient rhodium-catalyzed AH of a 2-enamidothiazole S66 (Scheme 46) using (S,S)-QuinoxP* L18a. The catalytic system was extended to a variety of 2-enamidoheteroarenes with excellent results (up to 99% ee), thus providing efficient access to 2-aminoethyl-arenes, which are useful building blocks in medicinal chemistry.…”
Section: Asymmetric Hydrogenation Of Enamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of a synthetic application, Evano's group recently developed a short and modular total synthesis of Conulothiazole A in 7 steps and 30% overall yield. 292 One of the key steps was an efficient rhodium-catalyzed AH of a 2-enamidothiazole S66 (Scheme 46) using (S,S)-QuinoxP* L18a. The catalytic system was extended to a variety of 2-enamidoheteroarenes with excellent results (up to 99% ee), thus providing efficient access to 2-aminoethyl-arenes, which are useful building blocks in medicinal chemistry.…”
Section: Asymmetric Hydrogenation Of Enamidesmentioning
confidence: 99%
“…As an example of a synthetic application, Evano’s group recently developed a short and modular total synthesis of Conulothiazole A in 7 steps and 30% overall yield . One of the key steps was an efficient rhodium-catalyzed AH of a 2-enamido-thiazole S66 (Scheme ) using ( S,S )-QuinoxP* L18a .…”
Section: Asymmetric Hydrogenation Of Enamidesmentioning
confidence: 99%
“…[ 114 ] It possesses a polyketide‐peptide structure with a aminoethylthiazole unit and a vinyl chloride group. Evano et al [ 115 ] reported its first synthesis involving the rhodium‐catalyzed enantioselective hydrogenation and vinylic Finkelstein reaction (Scheme 39). The carbocupration of compound 327 followed by iodolysis afforded the iodoalkene 328 as major ( E )‐isomer.…”
Section: Miscellaneous Approaches In Pgf Total Synthesis Of Naturamentioning
confidence: 99%
“…If a range of palladium-based catalysts have been shown to promote the carboxylation of benzylic halides to benzylic acids with carbon monoxide, a number of them however still suffer from competitive reduction or dimerization of the starting halides, and no general heterogeneous palladium catalyst has been reported, despite a strong potential in terms of catalyst separation and recovery as well as product contamination. In an attempt to address these limitations and based on our combined interests in metal catalysis and process chemistry, we became interested in developing an efficient, cheap, and general heterogeneous catalytic system for the carboxylation of benzylic bromides with carbon monoxide, and we report herein the results of our investigations.…”
Section: Introductionmentioning
confidence: 99%